Faktor-Faktor yang Mempengaruhi Stunting di Indonesia : Studi PRISMA (Preferred Reporting Items for Systematic Review & Meta Analysis). - Masdalena, Masdalena (Journal of Pharmaceutical and Sciences, 2024)
Stunting, a long-term nutritional problem that arises from insufficient food intake and is caused by vitamin deficiencies, has a broad and complex impact on children's health. Stunting can appear when the child is still in the womb and can occur until the child is two years old. This study explores the factors that influence stunting in Indonesia. Using the PRISMA (Preferred Reporting Items for Systematic Review & Meta-Analysis) method. Through a literature review from various sources such as Google Scholar and PubMed, this research aims to identify crucial factors related to stunting in toddlers by defining the keywords "stunting" and "stunting factors". In the identification, screening, eligibility, and analysis stages, 20 articles were selected that met the criteria for this research. Twenty (20) articles from 2019-2024 have been analysed using the PRISMA diagram. Articles from various journals were found to originate from Indonesia. Research studies show that the factors that influence stunting in Indonesia are 27.27 times compared to mothers with a higher level of education (aOR = 27.27; 95% CI = 4.37 to 170.11), with statistical significance (p = 0.00001). Internal factors influence stunting in Indonesia.